B2B MARKETING IN SUPPLY CHAIN DISRUPTION: BUILDING ADAPTIVE CAPABILITY THROUGH RELATIONAL GOVERNANCE AND DIGITAL INTEGRATION - Ismarini; Lukmanul Hakim; Tibrani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Supply chain disruptions have become increasingly frequent and complex, posing significant challenges for firms operating in B2B markets. Events such as pandemics, geopolitical conflicts, and environmental crises have exposed the limitations of traditional supply chain models, highlighting the need for greater adaptability and resilience. This study examines how relational governance and digital integration contribute to building adaptive capability in B2B marketing. Using a narrative literature review and conceptual framework development, the research synthesizes insights from academic literature, industry reports, and case studies related to supply chain disruption, relationship management, and digital transformation. The findings indicate that relational governance enhances trust, collaboration, and coordination among partners, reducing uncertainty and opportunistic behavior during disruptions. Digital integration, on the other hand, improves visibility, information sharing, and real-time decision-making, enabling faster and more effective responses. The interaction between these elements creates a synergistic effect that strengthens adaptive capability. The study also highlights the importance of flexibility and response speed as key dimensions of adaptability. A conceptual framework is proposed to explain how governance and digital integration jointly influence performance outcomes. The study concludes that integrating relational and technological capabilities is essential for achieving resilience and sustaining competitive advantage in dynamic B2B environments.